Farmer participatory research: Institutional considerations - Wortmann, Charles S.; Walker, F.R.; Ngambeki, D.S. (1994)
Farmer participatory research (FPR) is conducted to compliment conventional research approaches with two major objectives in mind: to increase the efficiency of developing and testing alternative technologies with subsequent improvement of production systems; and to improve the adaptive research capacity of the farmers. The relative amount of emphasis placed on these objectives needs consideration as it relates to how the FPR can best be structured. One option is for the FPR to be a part of the National Agricultural Research systems with on-golng FPR based at research locations. Another option may have as the primary objective the strengthening of farmers` capacity to modify their systems, which implies involving more farmers with a shorter period of intensive contact with a given group of farmers